FREQUENCY OF ANEMIA AMONG BREASTFED AND BOTTLE FEED CHILDREN (AGED UNDER 59 MONTHS) COMING TO THE KHYBER TEACHING HOSPITAL - Afridi, Aamir Karim; Shinwari, Lema; Raheem, Aizaz; Idress, Muhammad (Khyber Journal of Medical Sciences, 2025)
Objective: To determine the frequency of anemia in children under five years of age and to compare anemia status between breastfed and bottle-fed children. Methods: This cross-sectional study was conducted at the Pediatric Outpatient Department of Khyber Teaching Hospital, Peshawar, from August 19, 2024 to February 19, 2025. A total of 384 children aged under 59 months were enrolled through consecutive sampling. Children with chronic disease, blood transfusions, or iron supplementation were excluded. Demographic data, feeding practices and hemoglobin levels were recorded. Anemia was classified using WHO criteria into severe, moderate, mild and no anemia. Data were analyzed using SPSS version 20. Chi-square test was applied and p ? 0.05 was considered statistically significant. Results: Anemia was present in 241 children (62.8%). Moderate anemia was most frequent 143 (37.2%), followed by mild anemia 95 (24.7%) and severe anemia 3 (0.8%). Bottle-feeding was practiced by 269 (70.1%) children. No statistically significant association was found between anemia and feeding pattern (p = 0.97) or type of bottle feed (p = 0.83). Conclusion: Anemia was highly prevalent among children under five years, predominantly moderate and mild in severity, and was not significantly associated with feeding pattern. Broader nutritional, socioeconomic and behavioural determinants are likely responsible. Strengthening maternal and child nutrition practices, improving complementary feeding quality, and increasing access to iron-rich and fortified foods are essential strategies for reducing childhood anemia in this population.